A new member of the Pell sequences: The pseudo-Pell sequence - GÖKBAŞ, Hasan (Studia Universitatis Babeș-Bolyai Mathematica, 2025)
In this study, we define a new family of the Pell numbers and establish some properties of the relation to the ordinary Pell numbers. We give some identities the pseudo-Pell numbers. Moreover, we obtain the Binet’s formula, generating function formula and some formulas for this new type numbers. Moreover, we give the matrix representation of the pseudo-Pell numbers. Mathematics Subject Classification (2010): 11B37, 11B83, 11C20. Received 20 April 2024; Accepted 10 January 2025.